Analysis of Spatio-Temporal Variations of the Average Snow Cover During the Cold Seasons in the Northwest of Iran - Seyed Hossein Mirmousavi; Zahra Heidari Monfared (Nīvār)
In the current research, in order to investigate the spatial and temporal changes in the extent of snow cover in the northwest, the snow cover analysis data from the European Center for Medium-Range Weather Forecasts (ECMWF), version (ERA5) with a spatial resolution of 25 x 0.25 0.0 was received during the statistical period from 1982 to 2022 and then divided into four ten-year periods. In order to analyze spatial autocorrelation changes, global Moran indices and hot spot analysis (Getis-Ord Gi*) were used at the significance level of 90, 95 and 99%. Also, to determine the effect of temperature and snowfall on the amount of snow cover, the trend of changes in the average minimum temperature and monthly snowfall of 20 synoptic stations in the northwest region was investigated using the Mann-Kendall test and linear regression. The results of the present research showed that in the studied area, the snow cover has spatial autocorrelation and a strong cluster pattern. During the first decade to the end of the third decade, under the influence of the strong positive anomaly of the average minimum temperature (with an increasing trend), the amount of snow cover has decreased in all months of the cold season of the year, and sometimes in some months such as February (with threshold (the snow cover coefficient is 0.303 and higher) this trend of decreasing value is more noticeable. However, in the fourth decade, the amount and width (number of pixels) of snow cover has increased in all months of the cold season. With the point that the high values of the snow cover coefficient occurred in fewer ranges (number of pixels). The amount of precipitation in the 99th percentile has increased significantly during the last decade under study, and this has caused the snow cover to increase relatively compared to the first to third decades, although in general, the amount of snow cover In the whole area of the northwest, there has been a noticeable decrease during the last four decades.